PENGARUH NILAI OKTAN TERHADAP UNJUK KERJA MESIN DAN KAJIAN ANALISIS PEMBAKARAN AKIBAT DELAY COMBUSTION PADA MESIN OTTO SATU SILINDER - Radedo Ganda Halim; Abrar Riza; Steven Darmawan (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Gasoline is one type of fuel oil for two, three, and four wheeled motorized vehicles. Gasoline have two components, n-heptane (C7H16) and isooctane (C8H18). The quality of gasoline can be determined from amount of isooctane or which is also known as the octane number. Octane number is the number represents the volume percent of isooctane in gasoline. An octane number of 100 means that the gasoline is equivalent to pure isooctane in terms of combustion properties. While the octane number 0 means that the gasoline is equivalent to pure n-heptane. Octane number 92 means that the gasoline consists of 92% isooctane and 8% n-heptane. Nowdays, gasoline has appeared with various and higher octane numbers. The higher the number octane, the more efficient the process of burning the gasoline and selection of the wrong type of fuel oil can affect engine performance. For determine the performance, fuel conumption, on a vehicle, fuel testing is carried out on the Honda GX 160 engine to compare the results of fuel performance Pertalite (90), Pertamax (92), and Pertamax Turbo (98). In this test what will be carried out is to look for the efficiency of each fuel according to the RPM that has been determined, 1800, 2100, 2400, 2700, and 3000. So from each of these RPM you wil see the torque and time of reduced fuel consumption in 8mm tube. From there, you will see the comparison between each fuel, whether it is getting higher and more efficent or not. The increase that occurs in the delta h ratio between pertalite and Pertamax results in an increase of 7% at 2400 rpm, even though the initial torque of Pertalite is higher but the increase in Pertamax remains stable.